A capital idea: exploring the relationship between human and social capital and student achievement in schools. Issue 1 (10th December 2020) - Daly, Alan J.; Liou, Yi-Hwa; Der-Martirosian, Claudia
Abstract : Purpose: As accountability policies worldwide press for higher student achievement, schools across the globe are enacting a host of reform efforts with varied outcomes. Mounting evidence suggests reforms, which encourage greater collaboration among teachers, may ultimately support increased student learning. Specifically, this study aims to investigate the relationship between human and social and student achievement outcomes. Design/methodology/approach: In exploring this idea, the authors draw on human and social capital and examine the influence of these forms of capital on student achievement using social network analysis and hierarchical linear modeling. Findings: The results indicate that teacher human and social capital each have a significant and positive relationship with student achievement. Moreover, both teacher human and social capital together have an even stronger effect on student achievement than either human or social capital alone. Originality/value: As more schools across the globe adopt structures for teacher collaboration and the development of learning communities, there is a need to better understand how schools may capitalize on these opportunities in ways that yield improved student learning. Our work sheds new light on these critical foundational elements of human and social capital that are individually and collectively associated with student achievement.